2021
DOI: 10.1016/j.ejon.2021.102030
|View full text |Cite
|
Sign up to set email alerts
|

People with cancer and their family caregivers’ personal experience of using supportive eHealth technology: A narrative review

Abstract: To synthesise existing qualitative evidence regarding the experiences of people living with cancer and their family caregivers using eHealth technology in their home setting. Method: A narrative review using a systematic approach was utilised. Five databases (PubMed, CINAHL, EMBASE, PsycINFO and the Cochrane Library) were searched using a tailored search strategy to identify primary research articles published between January 2005 and May 2021. Studies were quality appraised using the Critical Appraisal Skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
5
17
0
Order By: Relevance
“…For many women, the ePRO pathway provided good connection/support, without the anxiety of attending hospital, and they were keen to continue. Similar themes have been evident in previous studies exploring nurse-led, telephone follow-up amongst gynaecological cancer patients [8, 9, 36] and ePRO use during active treatment [33]. The current study also showed a link between the practical logistics of ePRO pathway and the resulting personal impact.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For many women, the ePRO pathway provided good connection/support, without the anxiety of attending hospital, and they were keen to continue. Similar themes have been evident in previous studies exploring nurse-led, telephone follow-up amongst gynaecological cancer patients [8, 9, 36] and ePRO use during active treatment [33]. The current study also showed a link between the practical logistics of ePRO pathway and the resulting personal impact.…”
Section: Discussionsupporting
confidence: 88%
“…This work illuminates the feasibility results presented in Kennedy et al 2022 [29] by highlighting factors that in uenced women's readiness for a remote-based pathway, and the importance of building an ePRO service that continues to support and reassure women. This maps onto previous evidence highlighting the importance of individual's experiences and preferences of technology use in cancer care and implementation approaches for PRO integration and sustainability in routine care [32,33].…”
Section: Discussionmentioning
confidence: 54%
“…Presently, the patients described the Interaktor app as providing extra support during the treatment period by having easy access to self-care advice, information, and contact with the nurse if the symptoms were severe. The results are in line with those of the recent reviews where patients with cancer experienced apps as supportive tools that complemented or extended existing health care [39,40].…”
Section: Principal Findingssupporting
confidence: 89%
“…18 Mobile technologies can minimize the risk of exposure to COVID-19 and serve as alternative ways to communicate with the care recipient and LTC staff. 101,102 Family caregivers observe the advantages of technologies to support their roles, 99,[103][104][105][106] such as reducing caregiver stress by providing information, 99 supporting the mental and physical health of care recipients, and reducing and promoting interaction with LTC staff. 107 The demand for effective technologies to support caregivers will become more prominent.…”
Section: Accepted Manuscriptmentioning
confidence: 99%